2024
DOI: 10.1590/1519-6984.256565
|View full text |Cite
|
Sign up to set email alerts
|

Variations in soil physico-chemical properties, soil stocks, and soil stoichiometry under different soil layers, the major forest region Liupan Mountains of Northwest China

Abstract: Liupan Mountains are an important region in China in the context of forest cover and vegetation due to huge afforestation and plantation practices, which brought changes in soil physio-chemical properties, soil stocks, and soil stoichiometries are rarely been understood. The study aims to explore the distribution of soil nutrients at 1-m soil depth in the plantation forest region. The soil samples at five depth increments (0-20, 20-40, 40-60, 60-80, and 80-100 cm) were collected and analyzed for different soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…In this study, there were significant differences in the TP, AK, and SOM contents of different soil layers; TP was higher in the subsoil, and AK and SOM were higher in the topsoil ( Table 1 ). The soil physicochemical properties changed with increasing soil depth, and our results are consistent with the results of Rahman et al (2022) . Microbial secretions can significantly affect soil potassium availability ( Zorb et al, 2014 ), and factors such as microbial abundance and activity determine the pathway of soil litter conversion into SOM ( Witzgall et al, 2021 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, there were significant differences in the TP, AK, and SOM contents of different soil layers; TP was higher in the subsoil, and AK and SOM were higher in the topsoil ( Table 1 ). The soil physicochemical properties changed with increasing soil depth, and our results are consistent with the results of Rahman et al (2022) . Microbial secretions can significantly affect soil potassium availability ( Zorb et al, 2014 ), and factors such as microbial abundance and activity determine the pathway of soil litter conversion into SOM ( Witzgall et al, 2021 ).…”
Section: Discussionsupporting
confidence: 89%
“…From April 2021 to July 2022, we carried out an observational experiment in the Ziwuling Mountains, Loess Plateau, China, to record the monthly diurnal changes in R S and the monthly dynamic changes in soil microbial biomass and enzyme activity. Since soil physicochemical properties can vary significantly at different soil depths ( Rahman et al, 2022 ), we collected topsoil (0–30 cm) and subsoil (30–100 cm) respectively in the process of collecting soil samples. We hypothesized that the topsoil and subsoil physicochemical and microbial properties would be significantly different, and soil microbial properties would also change significantly in different months or seasons.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating the sampling depths (Table 2), there were significant differences among the attributes, except for pH and S, with higher values at the 0.0-0.2 m sampling depth due to routine chemical management to increase soil fertility. Several authors have observed that the physicochemical properties of soil change with increasing depth, indicating that depth influences the distribution and diversification of soil nutrients (Ali et al, 2019;Rahman et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Soil is still noted today as one of the environments in which there is the greatest amount of Bt spores (Dagga et al, 2016;Khodyrev et al, 2020). This environment has the ability to provide microhabitats that vary in their nutrient availability, in their physicochemical characteristics, in the characteristics of soil aggregates (Moreira and Siqueira, 2006), in intraspecific, interspecific interactions, and among the abiotic factors of the external environment and the soil itself (Cotta, 2016;Fierer, 2017;Rahman et al, 2024).…”
Section: Collection Of Soil For Analysis Of Fertility Soil Texture An...mentioning
confidence: 99%